Translocation of Mycobacterium tuberculosis after experimental ingestion. - Mustapha Fellag; Ahmed Loukil; Jamal Saad; Hubert Lepidi; Fériel Bouzid; Fabienne Brégeon; Michel Drancourt (PLoS ONE)
Human tuberculosis is a life-threatening infection following the inhalation of Mycobacterium tuberculosis, while the closely related bacteria Mycobacterium bovis and Mycobacterium canettii are thought to be transmitted by ingestion. To explore whether M. tuberculosis could also infect individuals by ingestion, male BALBc mice were fed 2 x 106 CFUs of M. tuberculosis Beijing or phosphate-buffered saline as a negative control, over a 28-day experiment. While eight negative control mice remained disease-free, M. tuberculosis was identified in the lymph nodes and lungs of 8/14 mice and in the spleens of 4/14 mice by microscopy, PCR-based detection and culture. Whole-genome sequencing confirmed the identity of the inoculum and the tissue isolates. In these genetically identical mice, the dissemination of M. tuberculosis correlated with the results of the culture detection of four intestinal bacteria. These observations indicate that ingested M. tuberculosis mycobacteria can translocate, notably provoking lymphatic tuberculosis.